Characteristics of hailstorms in the High Plains as deduced from 3-cm radar observations - Schleusener, Richard A., author; Marwitz, John D., author; Colorado State University, publisher (Colorado State University. Libraries, 1963)
Measurements were made of thunderstorm reflectivity structure in eastern Colorado from 15 May - 31 July 1962. Using a CPS-9 3-CM radar at Lowry AFB which was a stepped gain system, measurements were made of RHI tops, maximum reflectivity, elevation of maximum reflectivity, and reflectivity at 20, 30, and 40 thousand feet MSL. An analysis of variance was performed to determine whether significant (usually at the 5% level) differences occurred in these parameters between months or between categories of hail intensity. From the data presently available it appears possible to differentiate between hail and non-hail cases for June and July. It does not appear to be possible at this time to make this distinction in May, nor does it appear possible to differentiate between classifications of hail intensity, using either maximum hailstone diameter or "impact energy" values. Using another 3-CM radar at New Raymer, Colorado, the angles of "tilt" of radar echoes were determined from PPI positions of the tops of echoes and the positions of the points of maximum reflectivity at the base of the echoes. The azimuth of "tilt" of hail-producing cells was clockwise from the wind shear vector, and that of non-hail producing cells was counterclockwise from the wind shear vector. While these differences were not significantly different from zero, there was a significant difference in this angle for hail vs. non-hail cases. Higher mean reflectivities were found in the front than in the rear of precipitation echoes, and higher reflectivity values were found in the right-hand segment of precipitation echoes than in the left-hand segment.
CER63RAS18.
Keywords: Hailstorms -- Colorado